Two new species of the genus Chironephthya (Octocorallia, Alcyonacea, Nidaliidae, Siphonogorgiinae) from the Gulf of Thailand - Imahara, Yukimitsu; Chavanich, Suchana; Viyakarn, Voranop; Kushida, Yuka; Reimer, James D.; Fujita, Toshihiko (Zootaxa, 2020)
Two new species of the genus Chironephthya, C. sirindhornae sp. nov. and C. cornigera sp. nov., are described based on three specimens collected from the Gulf of Thailand. Both species are well distinguished from the previously described species of the genus Chironephthya by their colonies consisting of multiple stems that stand upright from a common base, and by a significantly thinner canal wall without large spindles. As a result of phylogenetic analyses using COI, mtMutS, and 28S rDNA sequences of these two species, these three specimens constituted an independent small clade within a large mixed clade of Siphonogorgia and Chironephthya, with the two species slightly different from each other. The discrepancy in the morphology suggested the erection of a new genus to accommodate these species, however, as the subclade was included in a large mixed clade of Siphonogorgia and Chironephthya, we place these species within genus Chironephthya. Our results further highlight the continuing confusion between Siphonogorgia and Chironephthya, and demonstrate the need for taxonomic revision of these genera.